1991
DOI: 10.1136/sti.67.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Anal human papillomavirus infection: a comparative study of cytology, colposcopy and DNA hybridisation as methods of detection.

Abstract: Considering surgical out-patient attenders with no history or signs of anal warts, 25% showed cytological evidence ofanal HPV infec-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…According to other investigators, Haye et al 22 and Frazer et al 23 cytology presents a sensitivity of 42% and 70%, respectively. However, in recent studies of Sonnex, 24 Fox et al, 25 and Goldstone et al 26 the sensitivity of cytology has been found to range between 83% to 98%, consistent to our results. It should be emphasized that in those later studies reporting high sensitivity rates, a different study design was followed, as HIV-positive patients and specimens with HGSIL cytology (hence more typical and obvious cellular changes) were also included.…”
Section: Discussionsupporting
confidence: 94%
“…According to other investigators, Haye et al 22 and Frazer et al 23 cytology presents a sensitivity of 42% and 70%, respectively. However, in recent studies of Sonnex, 24 Fox et al, 25 and Goldstone et al 26 the sensitivity of cytology has been found to range between 83% to 98%, consistent to our results. It should be emphasized that in those later studies reporting high sensitivity rates, a different study design was followed, as HIV-positive patients and specimens with HGSIL cytology (hence more typical and obvious cellular changes) were also included.…”
Section: Discussionsupporting
confidence: 94%
“…This could be due to airdrying artifact, which is common, or to the fact that koilocytosis appears less commonly in anal mucosal lesions than in their cervical counterparts. [12][13][14] Liquidbased preparations virtually eliminate all air drying and enhance koilocytotic changes. 17 Another positive aspect of anal cytology is the relative ease with which specimens are obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Several smaller studies have demonstrated that preinvasive lesions can be detected by cytology, and theoretical models of cost-effectiveness have also been published. [12][13][14] The use of anal smears from the area below the dentate line is recommended in patients at increased risk, such as HIV-positive people and women with genital tract squamous cell carcinoma (SCC). 15 If anal cytology is to gain acceptance, parameters of specimen adequacy will need to be defined and validated.…”
Section: A Highly Significant Association Between the Presence Of Colmentioning
confidence: 99%
“…Koilocytosis is less often seen at sites other than the cervix and in these cases the specificity of cytology is less well defined. 54 Presence of HPV DNA The polymerase chain reaction will frequently detect the presence of HPV DNA in clinical specimens which are normal on macroscopic and microscopic examination. This is often termed "latent" infection, although it is also appropriately classified as a subdivision of subclinical infection.…”
Section: Cytological and Histological Evidence Of Infectionmentioning
confidence: 99%